(untitled) (Journal of Environmental Science and Natural Resources, 2016)
Textile industries are the major contributor to environmental pollution and health hazards by generating huge amount of effluents that contain several pollutants and coloring agents. The concentration of these pollutants can be reduced to the permissible limit with the help of an Effluent Treatment Plant (ETP). The study was conducted to observe the textile effluent management techniques of an Effluent Treatment Plant (ETP) of Fakir Knitwear Limited (FKL), Narayanganj, Bangladesh. FKL set up a biological treatment plant to treat the effluent generated by the industry. Different effluent quality parameters were investigated at different stages in ETP. The effluent of the outlet was dark colored probably because of soluble coloring materials of the effluent but it is comparatively better than that of raw wastewater. There were found higher EC values than the standards which indicated that the greater amount of salts in the water due to dumping of solid wastes and discharging of industrial effluents. The highest TDS value 2054 ppm was observed at the screening pit unit than the other parts of the ETP. The highest DO was found 4.58 ppm in clarification tank which was within the standard value of aquaculture. The study also showed that the lowest BOD (24 ppm) and COD (145 ppm) was found at the outlet which was comparatively better than others. Although the effluent from the outlet contained pollutants, these effluent quality was comparatively good than the untreated waste water discharged from the industry. After treatment, the effluent of outlet moderately ensures the standard quality for aquaculture and irrigation. The results suggested that it is obvious to run the ETP regularly to improve the quality of effluents to save our native environment from the harmful effects of wastewater. J. Environ. Sci. & Natural Resources, 8(2): 25-31 2015